Pola Manajemen Kepala Sekolah dalam Membentuk Kepribadian Muslimah di SMA Islam Al-Ulum Terpadu Medan - Siti Fatimah; Hadi Saputra Panggabean; Manshuruddin Manshuruddin (Medan Resource Center, 2026)
This study investigates the principal’s managerial approach in shaping the personality of Muslim female students at Al-Ulum Integrated Islamic High School Medan amid the challenges of the digital era. The research aims to analyze how school leadership integrates Islamic values through structured keputrian (female student development) programs. A qualitative case study design was employed, with data collected through observations, interviews with principals, teachers, and students, and documentation analysis. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the principal implemented a value-based management model by systematically planning, organizing, supervising, and evaluating keputrian activities to foster students’ Islamic character, discipline, and moral awareness. The study also found that strong collaboration among the school foundation, teachers, parents, and an Islamic school environment significantly supported the program’s effectiveness. However, external social influences and uncontrolled technology use remained major challenges in developing students’ personalities. This study contributes a specific leadership-based management model for female Islamic character education in integrated Islamic schools. The findings imply that effective school leadership and structured religious programs can strengthen students’ moral development and resilience in the digital era.